Involvement of recB and recC genes of Escherichia coli in precise transposon excision. - Hickson, I D (1983)
The mutations texA343 and texA344, which increase transposon excision, are complemented by multicopy plasmids carrying recC+ and recB+, respectively, but not by derivative plasmids in which the recC and recB genes are inactivated. This shows that texA343 and texA344 are mutations in recC and recB, respectively.